2022
DOI: 10.1093/eurpub/ckac053
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of policies targeting dietary behaviours and physical activity: a systematic review of tools and outcomes

Abstract: Background Successful implementation of health policies require acceptance from the public and policy-makers. This review aimed to identify tools used to assess the acceptability of policies targeting physical activity and dietary behaviour, and examine if acceptability differs depending on characteristics of the policy and of the respondents. Methods A systematic review (PROSPERO: CRD42021232326) was conducted using three da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
(103 reference statements)
3
8
0
Order By: Relevance
“…As for sociodemographic differences in acceptability levels, our results are especially coherent with previous gender-based findings ( 12 , 16 ). Women’s greater odds of being in complete agreement with the targeted policies may be attributable to their overall greater levels of health consciousness ( 27 ) and their greater desire to adhere to Western society’s beauty ideals based on thin or fit body phenotypes ( 28 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As for sociodemographic differences in acceptability levels, our results are especially coherent with previous gender-based findings ( 12 , 16 ). Women’s greater odds of being in complete agreement with the targeted policies may be attributable to their overall greater levels of health consciousness ( 27 ) and their greater desire to adhere to Western society’s beauty ideals based on thin or fit body phenotypes ( 28 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results regarding variations in acceptability levels, based on examined policy, align with what is proposed by the Intervention Ladder, where an inverse relationship between policy acceptability and policy intrusiveness is observed ( 12 , 16 ). Unique to our study, we were also able to show jurisdictional differences in acceptability levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We conducted further meta- and systematic reviews that showed that (i) socio-cultural, economic and political contexts play a crucial role in successful policy implementation 42 , 43 and that (ii) highly intrusive measures like taxation or restrictions are least likely to be accepted when first implemented, but confidence in relevance and effectiveness increases over time, which in turn may increase acceptance. 44 We conducted scoping reviews on implementation processes of SSB taxation and physical activity policies to explore what happens after their enactment until possible effects are observed. Due to the small number of available studies, these two scoping maps did not allow firm conclusions about processes.…”
Section: Public Policies With Potential Influence On Food and Physica...mentioning
confidence: 99%